Presymptomatic viral shedding and infective ability of SARS-CoV-2; a case report. Issue 2 (February 2021) - Nissen, Karolina; Hagbom, Marie; Krambrich, Janina; Akaberi, Dario; Sharma, Sumit; Ling, Jiaxin; Hoffman, Tove; Lundkvist, Åke; Svensson, Lennart; Bondeson, Kåre; Salaneck, Erik
Abstract: Possible pre- or asymptomatic transmission has been reported, both from SARS-CoV and from MERS-CoV outbreaks, although this appears to be uncommon. In contrast, during the COVID-19 pandemic, an increasing number of studies and case reports indicate that pre- or asymptomatic transmission of SARS-CoV-2 is not only possible but also occurs frequently. We report repeated rRT-PCR detection of SARS-CoV-2 in a health care worker and demonstrate infective ability up to three days prior to mild COVID-19 symptoms. rRT-PCR indicated high viral levels approximately three days after exposure. Viral samples collected one and three days prior to symptoms exhibited infectivity on Vero E6 cells, confirmed by detection of double-stranded RNA by immunofluorescence, assessment of cytopathic effect (CPE) and rRT-PCR. SARS-CoV-2 specific IgM and IgG antibodies were detected by day 9 and 15, respectively, after symptom onset. We propose that this provides evidence for potential early presymptomatic transmission of SARS-CoV-2 and that infectivity may be manifest shortly after exposure. Abstract : SARS-CoV-2; COVID-19; Presymptomatic transmission; Cell culture; Infectivity; Antibody; Health care workers; Epidemiology; Coronavirus.